Effect of Tea Waste Supplementation in Feed on the Weight and Proportion of Liver and Pancreas in Male Quails - Aldiyanti, Amani; Tugiyanti, Elly; Wahyuningtyas, Amalina Nur (Bantara Journal of Animal Science, 2025)
The purpose of this study is to ascertain how adding fermented tea waste utilizing EM4 to male quail meals affects the weight and proportion of the pancreas and liver. One hundred four-week-old male quails (Coturnix coturnix japonica) make up the material. In vivo experimental techniques and a completely randomized design (RAL) were used in the study. Basal feed (T0), basal feed + 2% fermented tea powder waste (T1), basal feed + 2% fermented tea granule waste (T2), and basal + plus 2% fermented tea leaf waste (T3) are the treatments that were put to the test. The weight and proportion of the pancreas and liver are the variables that are being observed. The variance analysis's findings demonstrated that the liver percentage of male quails was not significantly impacted by the addition of fermented tea waste with EM4 to the meal. On the other hand, it significantly affected the male quail's liver weight. T0 is substantially different from T2 and T3, and T1 is significantly different from T2 and T3, according to the results of the Honest Significant Difference (HSD) test on the weight of male quail liver. The variance analysis's findings indicate that the weight and proportion of the pancreas are not significantly impacted by the addition of fermented tea waste in any manner. This study concludes that the supplementation of fermented tea waste (both granules and leaves) in the feed of male quails increases liver weight in male quails.